"The Eternal Question of Xenocratic Authorities": TheProblem of Early State Formation in Russian and BulgarianSchool Textbooks; 8th World Conference on Educational Sciences (WCES-2016) - Ageeva V. V. Vera Valentinovna (2016, 2016)
Title screen